A field study of indoor thermal comfort in the subtropical highland climate of Bogota, Colombia. (December 2015) - Natarajan, Sukumar; Rodriguez, Juan; Vellei, Marika
Abstract: This paper undertakes the first field study of indoor thermal comfort in Colombia. The objective of this study was to compare thermal comfort data gathered in office buildings in Bogota, Colombia with the predictions made by three well established standards: ISO 7730:2005 (PMV model), ANSI/ASHRAE Standard 55:2013 (adaptive model) and EN Standard 15251 (adaptive model). The study comprised the administration of a thermal assessment survey to 115 participants and the simultaneous measurement of indoor and outdoor physical variables in 3 offices having different ventilation regimes (natural ventilation, mechanical ventilation and mixed-mode i.e. both natural ventilation and air-conditioning). The findings show that the PMV model incorporated in the ISO 7730 as well as in the ASHRAE standard (which is the standard currently adopted in Colombia for regulating indoor environmental parameters) is able to describe comfort conditions in the mechanically ventilated (MV) office. In the case of the naturally ventilated office (NV), results indicate that the PMV model is not successful at estimating occupants' thermal sensations, and underestimates occupants' perception of discomfort. The EN 15251 adaptive model underestimates thermal discomfort in the NV and MM offices. The ASHRAE adaptive model shows similar patterns underestimating discomfort in the NV office. The findings provide robust evidence that the lack of perceived or actual control in low-energy naturally ventilated buildings strongly reduce occupants' thermal comfort and thus invalidate adaptive model predictions. Highlights: A field study investigated indoor thermal comfort in Colombia. The study included offices having three different ventilation regimes. PMV model sufficiently described thermal conditions in the mechanical ventilated and mixed-mode offices. PMV model was not successful at estimating the neutral operative temperature in the natural ventilated office. The lack of control in the naturally ventilated office reduced occupant thermal comfort.